Damage Mechanism and Wave Attenuation Induced by Blasting in Jointed Rock. (28th April 2022) - Song, Jie-Fang; Lu, Cai-Ping; Zhang, Xiu-Feng; Guo, Ying; Yang, Hong-Wei
Abstract : This work uses a combination of simulations performed via numerical models and field observations studied the attenuation of deep-hole blasting stress waves and the evolution mechanism of cracks in a jointed rock mass. First, we conclude that the larger the joint angle is, the larger is the transmission coefficient and smaller is the fractal dimension. Second, the time difference between the peak stress difference and the maximum principal stress on both sides of the blasting hole in the horizontal direction of the rock mass with joints is relatively large, but there is no significant difference in the vertical direction. Finally, an unjointed-rock-mass model and multiple parallel joint model are established to explore the attenuation of stress waves and damage effect of multiple joint rock mass, it is concluded that the larger the angle, the smaller is the particle peak velocity and amplitude attenuation, and as the number of stress waves passing through the joints increases, the amplitude gradually decreases and the high-frequency amplitude decreases more significantly than the low-frequency amplitude. The research conclusions of this paper further reveal the damage mechanism induced by a blasting stress wave on jointed rock masses and the law of stress wave propagation and attenuation.